2017
DOI: 10.1111/ppa.12797
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional profiling reveals no response of fungal pathogens to the durable, quantitative Lr34 disease resistance gene of wheat

Abstract: Durable resistance against fungal pathogens is highly valuable for disease management in agriculture. For its sustainable use, and to avoid pathogen adaptation, it is important to understand the underlying molecular mechanisms. Many studies on durable disease resistance in plants have focused exclusively on the host plant, whereas possible reactions and adaptations of pathogens exposed to this type of resistance have not been well researched. The wheat Lr34 gene, encoding a putative ABC‐transporter, provides b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Interestingly, an RNAseq study focusing on pathogens revealed no transcriptional response of P. triticina and B. graminis f.sp. hordei to the reduction of pathogen growth caused by the presence of Lr34res in wheat and barley, respectively (Sucher et al ., ). It is also possible that reduced local ABA concentrations in certain cells contribute to the Lr34res ‐mediated disease resistance.…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, an RNAseq study focusing on pathogens revealed no transcriptional response of P. triticina and B. graminis f.sp. hordei to the reduction of pathogen growth caused by the presence of Lr34res in wheat and barley, respectively (Sucher et al ., ). It is also possible that reduced local ABA concentrations in certain cells contribute to the Lr34res ‐mediated disease resistance.…”
Section: Discussionmentioning
confidence: 97%
“…In that regard, the results of this are consistent with previous studies. These previous studies used RNA sequencing methods to understand the response patterns of plants affected by pathogens (Rosli et al, 2013;Zeng et al, 2014;Sucher et al, 2017). However, little is known about the processes and mechanisms of Pdpap responses to F. oxysporum.…”
Section: Discussionmentioning
confidence: 99%
“…Two wheat adult plant resistance (APR) genes Lr34/Yr18/Sr57/Pm38 and Lr67/Yr46/Sr55/Pm46 are also examples of non-immunitymediated resistance genes (Krattinger et al, 2009;Moore et al, 2015). Both encode transporter proteins and confer resistance against multiple pathogens in wheat and can also function in other crops (Risk et al, 2013;Chauhan et al, 2015;Krattinger et al, 2016;Rinaldo et al, 2017;Schnippenkoetter et al, 2017;Sucher et al, 2018). These two genes have been important components of wheat breeding for rust resistance and often show additive or synergistic interactions with the other more "typical" R genes (immune receptors).…”
Section: Plant Resistance (R) Genesmentioning
confidence: 99%